Preparation method of porphyrinyl conjugated polymer with mesoporous structure as well as product and application of porphyrinyl conjugated polymer

Through solvent thermal synthesis and high temperature treatment, the pyrine -based polymer with a medium structure is prepared to solve the problem of the traditional CPS pore diameter distribution and insufficient use of functional groups, which significantly improves its performance in electrochemical and catalytic reactions.

CN119371619APending Publication Date: 2025-01-28SHANGHAI NAT ENG RES CENT FORNANOTECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411530482.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The relatively uniform pore size distribution in traditional conjugated polymers (CPs) limits its transport efficiency and adsorption capacity, and the insufficient utilization of functional groups hinders its effective application in electrochemical and catalytic reactions.

Method used

Through solvents thermal synthesis and high temperature treatment, raw materials such as silicone solution, pyrihin, and 1,4-phenyl-benzene formaldehyde are used to combine medium templates and structural-oriented assistants to prepare a pyrine-based polymer with melon structure.

Benefits of technology

It significantly improves the surface area and pore rate of the material, enhances its performance in electrochemical energy storage and catalytic reactions, and achieves excellent charge transmission characteristics and efficient quality transportation capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371619A_ABST
    Figure CN119371619A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a porphyrin-based conjugated polymer with a mesoporous structure as well as a product and application of the porphyrin-based conjugated polymer. A silica gel solution, pyrrole and 1, 4-terephthalaldehyde are adopted as starting raw materials, hydrochloric acid is adopted as a medium, and the porphyrin-based conjugated polymer (mPCPs) with the mesoporous structure is prepared through the technological processes of mixing, stirring and heat treatment by means of a mesoporous template and a solvothermal synthesis technology. The polymer has high specific surface area and optimized mass transfer characteristic, obviously enhances the anchoring performance of iodine-chlorine molecules, and shows excellent synergistic stability in the electron conversion process in the field of electrochemistry. The preparation method is simple and adjustable, the preparation cost is low, and large-scale production can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional material preparation, and in particular to a preparation method, product and application of a porphyrin-based conjugated polymer with a mesoporous structure. Background Art

[0002] As a new type of organic macromolecular material, conjugated polymers (CPs) exhibit excellent electrical conductivity and optoelectronic properties due to their continuous conjugated double bond structure and extensive π-electron delocalization. This makes CPs show great application potential in energy storage, catalysis, sensing and photoelectric conversion. However, the influence of the micromorphology of CPs on their overall performance cannot be ignored. The relatively uniform pore size distribution in traditional CPs limits their transport efficiency and adsorption capacity, thus failing to fully realize their potential in various applications. In addition, the insufficient utilization of functional groups in CPs hinders their ability to effectively participate in reactions involving complex mixtures, limiting their wide applicability in practical applications. Therefore, developing innovative strategies to enhance the functionality and versatility of CPs has become a necessary way to meet the complex challenges in different fields.

[0003] Studies have found that by adjusting the microstructure and distribution of functional groups of CPs, their performance in electrochemical and catalytic reactions can be significantly improved. For example, by using different synthesis methods and template technologies, CPs with a specific pore size distribution can be achieved, thereby improving their efficiency in electrochemical energy storage devices. At the same time, enhancing the accessibility of functional groups also helps to increase the participation of CPs in complex reactions. The patent of this invention provides a method for preparing a porphyrin-based conjugated polymer with a mesoporous structure. The method uses solvent thermal synthesis and subsequent high-temperature treatment as the main technical path. By precisely controlling the reaction conditions of silica gel solution, pyrrole and 1,4-terephthalaldehyde, a porphyrin-based conjugated polymer with a specific mesoporous structure is successfully prepared. The introduction of this mesoporous structure significantly increases the specific surface area and porosity of the material, thereby enhancing its performance in electrochemical energy storage and catalytic reactions. By optimizing the synthesis conditions, the precise regulation of the microscopic morphology of the polymer is achieved, so that the material exhibits excellent charge transfer characteristics and efficient mass transport capabilities in electrochemical applications. Summary of the invention

[0004] Porphyrin-based conjugated polymers with high specific surface area and mass transfer properties are currently a hot topic of research. The purpose of the present invention is to provide a method for preparing a mesoporous porphyrin-based conjugated polymer.

[0005] Another object of the present invention is to provide a mesoporous porphyrin-based conjugated polymer product prepared by the above method.

[0006] Another object of the present invention is to provide an application of the above product.

[0007] The object of the present invention is achieved by the following scheme: A method for preparing a porphyrin-based conjugated polymer with a mesoporous structure, using a silica gel solution, pyrrole and 1,4-terephthalaldehyde as starting materials, hydrochloric acid as a medium, through a process of mixing, stirring and heat treatment, with the help of a mesoporous template and solvent thermal synthesis technology, to prepare a porphyrin-based conjugated polymer (mPCPs) with a mesoporous structure, comprising the following steps: The nano-silica gel solution, pyrrole, 1,4-terephthalaldehyde and hydrochloric acid solution are mixed in proportion, the volume mixing ratio of the silica gel solution to the hydrochloric acid solution is (1-2):50, the amount of the pyrrole solution added is 0.5-0.8% of the volume of the mixed solution of the silica gel solution and the hydrochloric acid solution, and the molar ratio of the 1,4-terephthalaldehyde to the pyrrole solution is 1:2, then a structure-directing additive is added and stirred evenly, the obtained solution is transferred to a stainless steel high-pressure reactor with a polytetrafluoroethylene liner, and a solvent thermal reaction is carried out at 80°C for 24 hours, and then naturally cooled to room temperature; The samples were separated by centrifugation, then immersed in hydrofluoric acid solution for 30 min, and washed with ethanol and deionized water several times; After drying at 60 °C for 8 h, a porphyrin-based conjugated polymer material with a mesoporous structure was obtained.

[0008] The technical principle of the present invention is that after the mixed solution of silica gel solution, pyrrole and 1,4-terephthalaldehyde is mixed with hydrochloric acid, acetic acid is used as a structure-directing auxiliary agent to generate a porphyrin-based conjugated polymer precursor with a mesoporous structure, which is stirred at 80°C for 24 hours and gradually polymerized into a porphyrin-based conjugated polymer. Silica and excess ions are removed by repeated washing with hydrofluoric acid and ethanol; finally, a porphyrin-based conjugated polymer material with a mesoporous structure is formed.

[0009] Preferably, the particle size of the nano-silica gel solution is 12-40 nm.

[0010] Preferably, the auxiliary agent is one of acetic acid and propionic acid.

[0011] The present invention also provides a porphyrin-based conjugated polymer with a mesoporous structure, which is prepared according to any of the above methods.

[0012] The present invention also provides an application of a porphyrin-based conjugated polymer with a mesoporous structure in an electrode material of an electrochemical sensor, a supercapacitor or a battery.

[0013] Electrochemical performance test of porphyrin-based conjugated polymer material mPCP-40 with mesoporous structure: Taking the porphyrin-based conjugated polymer material mPCP-40 with mesoporous structure as the working electrode, simulate and verify its electrochemical performance in zinc-iodine battery. The method is: diffuse iodine and chlorine molecules into mPCPs by sublimation diffusion method to obtain ICl@mPCPs composite cathode, select zinc foil as anode, select 3M Zn(OTF)2 aqueous solution as electrolyte, and glass fiber as separator to construct a coin-type battery of Zn-I2 system, and test its electrochemical performance.

[0014] The present invention uses silica gel solution, pyrrole and 1,4-terephthalaldehyde as raw materials, and uses solvent thermal synthesis and drying process as the main technical path to synthesize porphyrin-based conjugated polymers with mesoporous structure. The material is applied in the field of electrochemistry and shows high electrochemical activity.

[0015] The advantage is that only solvent thermal synthesis and drying processes are used in the preparation process to self-assemble into a porphyrin-based conjugated polymer with a mesoporous structure. Performance tests show that the material shows high electrochemical activity in the field of electrochemistry. Therefore, the obtained polymer material has good development and application prospects.

[0016] The polymer obtained by the present invention has a high specific surface area and optimized mass transfer characteristics, significantly enhances the anchoring performance of iodine and chlorine molecules, and exhibits excellent synergistic stability in the electronic conversion process in the electrochemical field. The preparation method of the present invention is simple and adjustable, has low preparation cost, and can achieve large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a scanning electron microscope image of the porphyrin-based conjugated polymer material mPCP-40 with a mesoporous structure obtained in Example 1; Figure 2 The porphyrin-based conjugated polymer material mPCP-40 with a mesoporous structure obtained in Example 1 was -1 CV curve when Figure 3 This is the cyclic performance spectrum of the porphyrin-based conjugated polymer material mPCP-40 with a mesoporous structure obtained in Example 1. DETAILED DESCRIPTION

[0018] This embodiment is implemented on the premise of the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0019] Embodiment 1: A porphyrin-based conjugated polymer with a mesoporous structure is prepared by using a silica gel solution, pyrrole and 1,4-terephthalaldehyde as starting materials, hydrochloric acid as a medium, through a process of mixing, stirring and heat treatment, with the help of a mesoporous template and solvent thermal synthesis technology, and the porphyrin-based conjugated polymer (mPCPs) with a mesoporous structure is prepared according to the following steps: Accurately pipette 100 μL of silica gel solution with a particle size of 40 nm and 5 mL of 1M hydrochloric acid solution (the mixing ratio of silica gel solution to hydrochloric acid solution is 1:50 by volume), mix well, add 30 μL of pyrrole solution (the amount of pyrrole solution added is 0.6% of the volume of the mixed solution of the silica gel solution and the hydrochloric acid solution), stir well, add 1,4-terephthalaldehyde at a molar ratio of 1:2 to pyrrole, add 0.5 mL of acetic acid, stir continuously at 80°C for 24 hours, and cool naturally to room temperature; The silicon dioxide and excess ions were removed by centrifugation, and etching was performed with hydrofluoric acid, and the mixture was washed several times with ethanol and deionized water until it was neutral; The mixture was dried at 60° C. for 8 hours to obtain dry porphyrin-based conjugated polymer material mPCP-40 powder having a mesoporous structure.

[0020] Figure 1 is a scanning electron microscope image of the porphyrin-based conjugated polymer material mPCP-40 having a mesoporous structure obtained in Example, Figure 1 It can be seen that the material is composed of nanospheres with a mesoporous structure. The diameter of the sphere is about 150 nm, and the size of the mesopores is generally about 40 nm, forming an ordered mesoporous structure.

[0021] Electrochemical performance test of porphyrin-based conjugated polymer material mPCP-40 with mesoporous structure: Taking the porphyrin-based conjugated polymer material mPCP-40 with mesoporous structure as the working electrode, simulate and verify its electrochemical performance in zinc-iodine battery. The method is: use the sublimation diffusion method to diffuse iodine and chlorine molecules into mPCPs to obtain ICl@mPCPs composite cathode, use zinc foil as anode, select 3M Zn(OTF)2 aqueous solution as electrolyte, and glass fiber as separator to construct a coin-type battery of Zn-I2 system, and test its electrochemical performance.

[0022] Figure 2 The porphyrin-based conjugated polymer material mPCP-40 with a mesoporous structure obtained in this example has a 0.1 mV -1 The CV curve at Figure 2 It can be seen that the electrode prepared by this invention has good redox reversibility and structural stability.

[0023] Figure 3Graph showing the cycle performance of the porphyrin-based conjugated polymer material mPCP-40 having a mesoporous structure obtained in Example 1. Figure 3 It can be seen that the electrode prepared by this invention has good cycle stability.

[0024] Embodiment 2: A porphyrin-based conjugated polymer with a mesoporous structure is prepared in the following steps similar to those in Example 1: Accurately pipette 100 μL of silica gel solution with a particle size of 12 nm and 5 mL of 1M hydrochloric acid solution (the mixing ratio of silica gel solution to hydrochloric acid solution is 1:50 by volume), mix well, then add 30 μL of pyrrole solution (the amount of pyrrole solution added is 0.6% of the volume of the mixed solution of the silica gel solution and the hydrochloric acid solution), stir well, add 1,4-terephthalaldehyde at a molar ratio of 1:2 to pyrrole, add 0.5 mL of acetic acid, stir continuously at 80°C for 24 hours, and cool naturally to room temperature; The silicon dioxide and excess ions were removed by centrifugation, and etching was performed with hydrofluoric acid, and the mixture was washed several times with ethanol and deionized water until it was neutral; The mixture was dried at 60° C. for 8 hours to obtain dry porphyrin-based conjugated polymer material mPCP-12 powder having a mesoporous structure.

[0025] Embodiment 3: A porphyrin-based conjugated polymer with a mesoporous structure is prepared in the following steps similar to those in Example 1: Accurately pipette 150 μL of silica gel solution with a particle size of 40 nm and 5 mL of 1M hydrochloric acid solution (the mixing ratio of silica gel solution to hydrochloric acid solution is 3:100 by volume), mix well, then add 30 μL of pyrrole solution (the amount of pyrrole solution added is 0.6% of the volume of the mixed solution of the silica gel solution and the hydrochloric acid solution), stir well, add 1,4-terephthalaldehyde at a molar ratio of 1:2 to pyrrole, add 0.5 mL of propionic acid, stir continuously at 80°C for 24 hours, and cool naturally to room temperature; The silicon dioxide and excess ions were removed by centrifugation, and etching was performed with hydrofluoric acid, and the mixture was washed several times with ethanol and deionized water until it was neutral; The mixture was dried at 60° C. for 8 hours to obtain dry porphyrin-based conjugated polymer material mPCP-40 powder having a mesoporous structure.

[0026] Embodiment 4: A porphyrin-based conjugated polymer with a mesoporous structure is prepared in the following steps similar to those in Example 1: Accurately pipette 100 μL of 22 nm silica gel solution and 5 mL of 1M hydrochloric acid solution (the mixing ratio of silica gel solution to hydrochloric acid solution is 1:50 by volume), mix well, then add 30 μL of pyrrole solution (the amount of pyrrole solution added is 0.6% of the volume of the mixed solution of the silica gel solution and the hydrochloric acid solution), stir well, add 20 mg of 1,4-terephthalaldehyde at a molar ratio of 1:2 to pyrrole, add 0.5 mL of acetic acid, stir continuously at 70°C for 24 hours, and cool naturally to room temperature; The silicon dioxide and excess ions were removed by centrifugation, and etching was performed with hydrofluoric acid, and the mixture was washed several times with ethanol and deionized water until it was neutral; The mixture was dried at 60° C. for 8 hours to obtain dry porphyrin-based conjugated polymer material mPCP-22 powder having a mesoporous structure.

[0027] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a porphyrin-based conjugated polymer having a mesoporous structure, characterized in that , using silica gel solution, pyrrole and 1,4-terephthalaldehyde as starting materials, hydrochloric acid as medium, through the process of mixing, stirring and heat treatment, with the help of mesoporous template and solvent thermal synthesis technology, porphyrin-based conjugated polymers (mPCPs) with mesoporous structure are prepared, including the following steps: The nano-silica gel solution, pyrrole, 1,4-terephthalaldehyde and hydrochloric acid solution are mixed in proportion, the volume mixing ratio of the silica gel solution to the hydrochloric acid solution is (1-2):50, the amount of the pyrrole solution added is 0.5-0.8% of the volume of the mixed solution of the silica gel solution and the hydrochloric acid solution, and the molar ratio of the 1,4-terephthalaldehyde to the pyrrole solution is 1:2, then a structure-directing additive is added and stirred evenly, the obtained solution is transferred to a stainless steel high-pressure reactor with a polytetrafluoroethylene liner, and a solvent thermal reaction is carried out at 80°C for 24 hours, and then naturally cooled to room temperature; The samples were separated by centrifugation, then immersed in hydrofluoric acid solution for 30 min, and washed with ethanol and deionized water several times; After drying at 60 °C for 8 h, a porphyrin-based conjugated polymer material with a mesoporous structure was obtained.

2. The method for preparing a porphyrin-based conjugated polymer having a mesoporous structure according to claim 1, characterized in that: The particle size of the nano silica gel solution is 12-40 nm.

3. The method for preparing a porphyrin-based conjugated polymer having a mesoporous structure according to claim 1, characterized in that: The structure-directing auxiliary agent is one of acetic acid and propionic acid.

4. The method for preparing a porphyrin-based conjugated polymer having a mesoporous structure according to any one of claims 1 to 3, characterized in that: Prepare as follows: Accurately pipette 100 μL of silica gel solution with a particle size of 40 nm and 5 mL of 1M hydrochloric acid solution (the mixing ratio of silica gel solution to hydrochloric acid solution is 1:50 by volume), mix well, add 30 μL of pyrrole solution (the amount of pyrrole solution added is 0.6% of the volume of the mixed solution of the silica gel solution and the hydrochloric acid solution), stir well, add 1,4-terephthalaldehyde at a molar ratio of 1:2 to pyrrole, add 0.5 mL of acetic acid, stir continuously at 80°C for 24 hours, and cool naturally to room temperature; The silicon dioxide and excess ions were removed by centrifugation, and etching was performed with hydrofluoric acid, and the mixture was washed several times with ethanol and deionized water until it was neutral; The mixture was dried at 60° C. for 8 hours to obtain dry porphyrin-based conjugated polymer material mPCP-40 powder having a mesoporous structure.

5. The method for preparing a porphyrin-based conjugated polymer having a mesoporous structure according to any one of claims 1 to 3, characterized in that: Prepare as follows: Accurately pipette 100 μL of silica gel solution with a particle size of 12 nm and 5 mL of 1M hydrochloric acid solution (the mixing ratio of silica gel solution to hydrochloric acid solution is 1:50 by volume), mix well, then add 30 μL of pyrrole solution (the amount of pyrrole solution added is 0.6% of the volume of the mixed solution of the silica gel solution and the hydrochloric acid solution), stir well, add 1,4-terephthalaldehyde at a molar ratio of 1:2 to pyrrole, add 0.5 mL of acetic acid, stir continuously at 80°C for 24 hours, and cool naturally to room temperature; The silicon dioxide and excess ions were removed by centrifugation, and etching was performed with hydrofluoric acid, and the mixture was washed several times with ethanol and deionized water until it was neutral; The mixture was dried at 60° C. for 8 hours to obtain dry porphyrin-based conjugated polymer material mPCP-12 powder having a mesoporous structure.

6. The method for preparing a porphyrin-based conjugated polymer having a mesoporous structure according to any one of claims 1 to 3, characterized in that: Prepare as follows: Accurately pipette 150 μL of silica gel solution with a particle size of 40 nm and 5 mL of 1M hydrochloric acid solution (the mixing ratio of silica gel solution to hydrochloric acid solution is 3:100 by volume), mix well, then add 30 μL of pyrrole solution (the amount of pyrrole solution added is 0.6% of the volume of the mixed solution of the silica gel solution and the hydrochloric acid solution), stir well, add 1,4-terephthalaldehyde at a molar ratio of 1:2 to pyrrole, add 0.5 mL of propionic acid, stir continuously at 80°C for 24 hours, and cool naturally to room temperature; The silicon dioxide and excess ions were removed by centrifugation, and etching was performed with hydrofluoric acid, and the mixture was washed several times with ethanol and deionized water until it was neutral; The mixture was dried at 60° C. for 8 hours to obtain dry porphyrin-based conjugated polymer material mPCP-40 powder having a mesoporous structure.

7. The method for preparing a porphyrin-based conjugated polymer having a mesoporous structure according to any one of claims 1 to 3, characterized in that: Prepare as follows: Accurately pipette 100 μL of 22 nm silica gel solution and 5 mL of 1M hydrochloric acid solution (the mixing ratio of silica gel solution to hydrochloric acid solution is 1:50 by volume), mix well, then add 30 μL of pyrrole solution (the amount of pyrrole solution added is 0.6% of the volume of the mixed solution of the silica gel solution and the hydrochloric acid solution), stir well, add 20 mg of 1,4-terephthalaldehyde at a molar ratio of 1:2 to pyrrole, add 0.5 mL of acetic acid, stir continuously at 70°C for 24 hours, and cool naturally to room temperature; The silicon dioxide and excess ions were removed by centrifugation, and etching was performed with hydrofluoric acid, and the mixture was washed several times with ethanol and deionized water until it was neutral; The mixture was dried at 60° C. for 8 hours to obtain dry porphyrin-based conjugated polymer material mPCP-22 powder having a mesoporous structure.

8. A porphyrin-based conjugated polymer having a mesoporous structure, characterized in that Prepared according to any one of claims 1 to 7.

9. Use of the porphyrin-based conjugated polymer with a mesoporous structure according to claim 8 in an electrode material for an electrochemical sensor, a supercapacitor or a battery.